EFEKTIVITAS PROGRAM KARTU TANI DALAM PENYALURAN PUPUK BERSUBSIDI DI KECAMATAN MAPILLI KABUPATEN POLEWALI MANDAR - Marindang, Selfi; Setiawati, Budi; Wahid, Nur (Universitas Muhammadiyah Makassar, 2023)
The purpose of this study was to determine the effectiveness of the farmer card program in distributing subsidized fertilizers in Mapilli district, Polewali Mandar regency.The research method used is a qualitative method, usually the data is inductive or qualitative, then the results of this study use a qualitative type that emphasizes a generalization and the type of research used is a descriptive type which will provide an overview or a detailed phenomenon regarding the effectiveness of the farmer card program in distribution. subsidized fertilizer in Mapilli District, Polewali Mandar regency.The results of this study indicate that the application of farmer cards in the distribution of subsidized fertilizers in Mapilli District, Polewali Mandar regency. The farmer cards that have been implemented in early 2021 until now, this electronic-based program is considered difficult to use among farmers who are 50 years old and over and still show results that are not maximized so it can be said that farmer cards in Mapilli District are not effective. The Farmer card program which is a policy from the Ministry of Agriculture as outlined in the Regulation of the Minister of Agriculture (Permentan) Number 10 of 2020 concerning the highest allocation and retail price of subsidized fertilizer and also a national program.